1974
DOI: 10.1177/00220345740530051201
|View full text |Cite
|
Sign up to set email alerts
|

On the Static Creep of Dental Amalgam

Abstract: A new equation is proposed for the description of the static creep of dental amalgam. It is satisfactory for a wide range of stresses and strain rates in static creep experiments during steady state. The hypothesis was confirmed that creep of dental amalgam is determined by the low melting phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1977
1977
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…3). These creep results are in agreement with the data given by VRIJHOEF & DRIESSENS (1975), who investigated the dependence of the creep rate for three dental amalgams on aging at 37°C for 1 year. Assuming a chemical composition of ^, as given by ESPEVIK (1977) (Hg 51, Ag 41, Sn 8 wt-%), stoichiometric calculations performed on a conventional amalgam in chemical equilibrium gave a ratio between amounts in weight units of p^ and y^ of about 10:1.…”
Section: Resultssupporting
confidence: 92%
“…3). These creep results are in agreement with the data given by VRIJHOEF & DRIESSENS (1975), who investigated the dependence of the creep rate for three dental amalgams on aging at 37°C for 1 year. Assuming a chemical composition of ^, as given by ESPEVIK (1977) (Hg 51, Ag 41, Sn 8 wt-%), stoichiometric calculations performed on a conventional amalgam in chemical equilibrium gave a ratio between amounts in weight units of p^ and y^ of about 10:1.…”
Section: Resultssupporting
confidence: 92%
“…The effective stress (applied stress minus an internal stress component) was considered when VRIJHOEF & DRIESSENS (1974) evaluated creep as a function of stress and temperature of dental amalgam. They concluded that creep of dental amalgam was determined by the low melting phases.…”
Section: (Acceptedfir Publication !I May 1977)mentioning
confidence: 99%
“…1 has been used by Vrijhoef and Driessens (1974a) and by Hero (1983) where the effective stress, c 0-cfo consisting of the applied stress minus an internal or back stress, is substituted for a7. As a result, values of the stress exponent were found to be about 2.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, values of the stress exponent were found to be about 2. The activation energy was 109 kI/mol for six amalgams (Vrijhoef and Driessens, 1974a).…”
Section: Introductionmentioning
confidence: 99%